Charlotte Brontë and defensive conduct : the author and the body at risk - Gezari, Janet (University of Pennsylvania Press, 1992)
In both her life and her art, Charlotte Bronte was alive to the difficulty of responding to attacks that are denied or under-acknowledged, so that any defense risks seeming defensive in our modern sense of the word: too quick to take offense or covertly aggressive. For some, Bronte's novels are deformed by hunger, rebellion, and rage; for others, they are deformed by the repression of these feelings. Both views ignore hunger, rebellion, and rage as powerful resources for Bronte's art rather than as personal difficulties to be surmounted or even deplored. Janet Gezari reassesses Charlotte Bronte's achievement by showing the ways in which an embodied defensiveness is central to both the novels and their author's life. She argues that Bronte's novels explore the complex relations between accommodation and resistance in the lives of those who find themselves - largely for reasons of class and gender - on the defensive. Gezari rehabilitates the concept of defensiveness by suggesting that there are circumstances in which defensive conduct is both appropriate and creditable. The emphasis on a different kind of bodily experience in each novel identifies Bronte's specific social concerns in the text, and the kinds of self-defenses at issue in it. This book arrives in the wake of renewed critical interest in Charlotte Bronte, especially on the part of feminist critics. They have substantially revised our understanding of Jane Eyre and Villette, but there have been few studies of The Professor and Shirley, and few book-length studies of Charlotte Bronte's work as a whole. Although Gezari's book is not a biography, she also seeks to revise our sense of Bronte's life by turning attention from its familiar romantic circumstances - the bleakness of the Yorkshire moors and unrequited love - to its less familiar practical circumstances - her struggles as a woman of a certain class and a publishing author. They reveal a woman more embattled, contentious, and resilient, though no less passionate, than the more familiar trembling soul.